AN EFFICIENT SYNTHESIS OF 1,3-BENZODIAZINE-2,4-DIONES ANALOGS - Fredryk Mandey (Indonesian Journal of Chemistry, 2001)
An investigation of base promoted reaction of phenylanthranilate and isocyanate has been carried out. The reaction between phenylanthranilate (11) and phenylisocyanate and n-butylisocyanate gave remarkable yields of corresponding 1,3-Benzo-diazine-2,4-diones (12a) and (12b).